Carbon/Phenolic Nanocomposites as Advanced Thermal Protection Material in Aerospace Applications. (6th June 2013) - Tate, J. S.; Gaikwad, S.; Theodoropoulou, N.; Trevino, E.; Koo, J. H.
Abstract : Ablative nanocomposites were prepared by incorporating multiwall carbon nanotubes (MWCNT) into phenolic resin and then impregnating them into rayon-based carbon fabric. MWCNT were blended into phenolic resin at 0.5, 1, and 2 wt% loadings using a combination of sonication and high shear mixing to insure uniform dispersion of MWCNT. The composite test specimens were tested by using an oxyacetylene test bed (OTB) applying a heat flux of 1000 W/cm 2 for duration of 45 seconds. Composite specimens with 2 wt% MWCNT showed reduction in mass loss, recession in length, and in situ temperatures compared to control composites.